Training evaluation levels and ROI: the case of a small logistics company. Issue 9 (28th October 2014) - Curado, Carla; Martins Teixeira, Susana
Abstract : Purpose: – This study's purpose is to contribute to literature on training evaluation following Kirkpatrick's four-levels model and estimating each training program's return on investment (ROI) using evidence from a small firm. Design/methodology/approach: – This case study uses data collected at a logistics company based upon training output indicators like training program evaluation data; individual performance evaluation reports; information on attained objectives; service and productivity levels; quality audit reports; and accounting data. Findings: – Results show that all the training programs addressed report evaluation procedures at the four different levels (reactions, learning, behavior and results). ROI for each training program was estimated based upon costs and benefits associated to each program. The two training programs presenting above-average returns address work quality and conditions. The program addressing corporate social responsibility issues produced below-average results. Research limitations/implications: – Limitations to this study may result from collecting data in a single moment in time and using data from a single organization, excluding generalization and extrapolation of results. Practical implications: – This case study should inspire managers in small and medium enterprises (SME) to implement training evaluation practices and ROI estimation. Having the ROI estimation available allows better management of the training budget, as ROI's presentation is an argument to assign value and progress. Originality/value: – The originality of this study regards the way it reports training evaluation practices at the four levels established by Kirkpatrick's framework (2005) and complements it with ROI estimation regarding five training courses run at a Portuguese SME logistics firm.